Bedload Sediment Concentration of Sungai Kahang Downstream Kahang Dam in Johor - Adnan, Mohd Shalahuddin; Nda, Muhammad; Mohammad Razi, Mohd Adib; Mohd Yusoff, Mohd Azlan; Rahmat, Siti Nazahiyah; Abustan, Muhammad Salleh; Ahmad Tajudin, Saiful Azhar (International Journal of Integrated Engineering, 2018)
Dams construction globally on rivers have generated a significant adjustment to stream hydrology and sediment dynamics. The impoundment of rivers by dam reservoirs will trap the sediments following freely downstream the river channel. Kahang dam is constructed to impound Sungai Kahang (Kahang River) for water supply purposes; this may have adverse effects downstream the dam by starving the river its natural sediments and changing the river flow. This study evaluates the bedload sediments and river discharge downstream the dam by taking field measurements, using the area-velocity and single increment method at three selected gauging locations (St0, St1, St2). The results obtained between January and July 2017 show the highest bedload discharge for all the gauging Stations to be 0.0736 tones/day at St0 and 0.0077 tones/day at St2 while the river flow remains relatively steady between 0.528 m3/s to 2.534 m3/s. The high bedload discharge recorded can be attributed to the anthropogenic activities going on during external construction works going on, as lower bedload concentration values followed immediately after the external construction work was completed.